Impaired alternative macrophage differentiation of peripheral blood mononuclear cells from obese subjects - Bories, Gael (Sage Publications, 2012)
Visceral obesity, a chronic, low-grade inflammatory disease, predisposes to the metabolic syndrome, type 2 diabetes and its cardiovascular complications. Adipose tissue is not a passive storehouse for fat, but an endocrine organ synthesizing and releasing a variety of bioactive molecules, some of which are produced by infiltrated immune-inflammatory cells including macrophages. Two different sub-populations of macrophages have been identified in adipose tissue: pro-inflammatory “classical” M1 and anti-inflammatory “alternative” M2 macrophages and their ratio is suggested to influence the metabolic complications of obesity. These macrophages derive primarily from peripheral blood mononuclear cells (PBMC). We hypothesized that obesity and the metabolic syndrome modulate PBMC functions. Therefore, alteration of the monocyte response, and more specifically their ability to differentiate toward alternative anti-inflammatory macrophages was assessed in PBMC isolated from lean and obese subjects with or without alterations in glucose homeostasis. Our results indicate that PBMC from obese subjects have an altered expression of M2 markers and that their monocytes are less susceptible to differentiate toward an alternative phenotype. Thus PBMC in obesity are programmed, which may contribute to the inflammatory dysregulation and increased susceptibility to inflammatory diseases in these patients.